Amelioration by glycine of brain damage in neonatal rat brain following hypoxia–ischemia. Issue 3 (24th January 2017) - Mori, Hiroko; Momosaki, Ken; Kido, Jun; Naramura, Tetsuo; Tanaka, Kenichi; Matsumoto, Shirou; Nakamura, Kimitoshi; Mitsubuchi, Hiroshi; Endo, Fumio; Iwai, Masanori
Abstract: Background: Glycine protected adult brains against injury in an experimental model of stroke, but, because the ischemic response of neonatal brains differs from that of adult brains, we examined the neuroprotective efficacy of glycine and associated mechanisms in an experimental model of neonatal hypoxic–ischemic (HI) encephalopathy. Methods: Neonatal (postnatal day 7) Wistar rats were randomly divided into an untreated group (non‐HI) and two HI groups that were treated with left common carotid artery ligation and saline control or glycine. After recovery, pups that received surgery were injected i.p. with saline or glycine (800 mg/kg; optimal dose determined in pilot experiments) and were placed in a controlled 8% O2 chamber for 120 min. Brains were harvested at various times after return to normoxia (several hours–days after HI) for analysis of infarct area, glial activation, cell apoptosis, and tumor necrosis factor‐α (TNF‐α) expression on histology and reverse transcription–polymerase chain reaction. Results: Glycine injections induced large (approx. 15‐fold) but brief (approx. 2 h) increases in cerebrospinal fluid concentrations. In particular, the glycine group had a >70% decrease in infarct areas compared with controls at 7 days after HI. Glycine also significantly reduced astrocyte reactive transformation, microglia activation, and terminal deoxynucleotidyl transferase dUTP nick end labeling‐positive (apoptotic) cell numbers in peri‐lesional areas at 3 days after HI, and TNF‐α mRNA expression in the injured hemisphere at 12 and 24 h after HI. Conclusion: Glycine protected neonatal rat brains against HI, in part by inhibiting TNF‐α‐induced inflammation and gliosis. Hence, systemic glycine infusions may have clinical utility for the treatment of HI injury in human newborns.